8.2k views
0 votes
PLEASE SOMEONE ANSWER I'VE ASK THIS QUESTION 3 TIMES AND NO ONE ANSWERS ME.

A. Write an expression based on the given statement

b. Simplify the expression you just wrote
------
1. Find the sum of -7g and 4g + 2

2. Find the difference when 6ん is subtracted from 2ん - 4

User Dor Cohen
by
5.6k points

1 Answer

2 votes

Answer:

1 a)
-7g+4g+2

1 b)
-3g+2

2 a)
2\lambda-4-6\lambda

2 b)
-4\lambda-4

Explanation:

Given statements:

1. Find the sum of -7g and 4g + 2

2. Find the difference when 6
\lambda is subtracted from 2
\lambda - 4

a) To write an expression based on the given statement

b) To simplify the expression

Solution:

1) The expression for sum of
-7g and
4g+2 is given as:

1 a)
-7g+4g+2

The above expression can be simplified by combining the like terms:

1 b) ⇒
-3g+2 [ As
-7g+4g=-3g ]

2) The expression for the difference when
6\lambda is subtracted from
2\lambda-4 can be given as:

2 a)
2\lambda-4-6\lambda

The above expression can be simplified by combining the like terms:

2 b) ⇒
-4\lambda-4 [ As
2\lambda-6\lambda = -4\lambda ]

User Daiana
by
5.1k points
Welcome to QAmmunity.org, where you can ask questions and receive answers from other members of our community.